Nursing Service Management Evaluation in the Medical Ward of a Type B Non-Government Hospital - Simanjuntak, Samuel Maju; Simatupang, Ika Prika; Ludji, Sarlince; Sinaga, Rodina; Marpaung, Jannice (Universitas Padjadjaran, 2025)
Effective nursing service management is essential to ensuring high-quality healthcare delivery in hospitals. This study aimed to evaluate the nursing service management in the medical ward of a type B private hospital in Bandung, Indonesia, using a qualitative research approach. The intervention focused on analyzing key managerial functions—planning, organizing, directing, staffing, and controlling—and identifying challenges encountered in nursing service implementation. The primary methods included in-depth interviews and participatory observations involving the head nurse and staff nurses. Qualitative findings revealed several issues, such as uneven workload distribution, a shortage of nursing staff, and the suboptimal application of digital nursing documentation via the Electronic Medical Record (EMR) system. To validate these findings, data triangulation was conducted using document analysis, workload records, and a patient satisfaction survey. Results from the survey involving 33 patients showed that 78.8% expressed satisfaction with the nursing care they received. A SWOT analysis identified strengths in team collaboration and infrastructure support; weaknesses in human resources and digital documentation skills; opportunities through management support and ongoing training; and threats in the form of resistance to system changes. This study recommends optimizing EMR documentation training, restructuring workload distribution, and fostering a supportive work environment to improve the quality of nursing care. Keywords: Management evaluation, medical ward, nursing care.